Prosociality and Social Responsibility Were Associated With Intention of COVID-19 Vaccination Among University Students in China - Yanqiu Yu; Sitong Luo; Phoenix Kit-han Mo; Suhua Wang; Junfeng Zhao; Guohua Zhang; Lijuan Li; Liping Li; Joseph Tak-fai Lau (Kerman University of Medical Sciences, 2022)
Background  Coronavirus disease 2019 (COVID-19) vaccination is expected to end the pandemic; a high coverage rate is required to meet this end. This study aimed to investigate the prevalence of behavioral intention of free/self-paid COVID-19 vaccination and its associations with prosociality and social responsibility among university students in China. Methods  An anonymous online cross-sectional survey was conducted among 6922 university students in five provinces in China during November 1-28, 2020. With informed consent, participants filled out an online survey link distributed to them via WeChat study groups. The response rate was 72.3%.Results  The prevalence of behavioral intentions of free COVID-19 vaccination was 78.1%, but it dropped to 57.7% if the COVID-19 vaccination involved self-payment (400 RMB; around 42 USD). After adjusting for background factors, prosociality (free vaccination: adjusted odds ratio [ORa] = 1.10, 95% CI: 1.09-1.12; self-paid vaccination: ORa = 1.08, 95% CI: 1.07-1.09) and social responsibility (free vaccination: ORa = 1.17, 95% CI: 1.14-1.19; self-paid vaccination: ORa = 1.13, 95% CI: 1.11-1.14) were positively associated with the two variables of COVID-19 vaccination intention.Conclusion  The present study demonstrated the positive effects of prosociality and social responsibility on the intention of COVID-19 vaccination. Accordingly, modification of prosociality and social responsibility can potentially improve COVID-19 vaccination. Future longitudinal and intervention studies are warranted to confirm such associations across populations and countries.